Neutralizing antibodies to SARS‐CoV‐2 Omicron variant after third mRNA vaccination in health care workers and elderly subjects - Haveri, Anu; Solastie, Anna; Ekström, Nina; Österlund, Pamela; Nohynek, Hanna; Nieminen, Tuomo; Palmu, Arto A.; Melin, Merit (European journal of immunology, 2022)
The emergence of SARS‐CoV‐2 Omicron variant (B.1.1.529) with major spike protein mutations has raised concern over potential neutralization escape and breakthrough infections among vaccinated and previously SARS‐CoV‐2‐infected subjects. We measured cross‐protective antibodies against variants in health care workers (HCW, n = 20) and nursing home residents (n = 9) from samples collected at 1–2 months, following the booster (3rd) dose. We also assessed the antibody responses in subjects infected before the Omicron era (n = 38) with subsequent administration of a single mRNA vaccine dose. Following booster vaccination, HCWs had high IgG antibody concentrations to the spike protein and neutralizing antibodies (NAb) were detectable against all variants. IgG concentrations among the elderly remained lower, and some lacked NAbs against the Beta and Omicron variants. NAb titers were significantly reduced against Delta, Beta, and Omicron compared to WT virus regardless of age. Vaccination induced high IgG concentrations and variable titers of cross‐reactive NAbs in previously infected subjects, whereas NAb titers against Omicron were barely detectable 1 month postinfection. High IgG concentrations with cross‐protective neutralizing activity were detected after three Coronavirus Disease 2019 (COVID‐19) vaccine doses in HCWs. However, lower NAb titers seen in the frail elderly suggest inadequate protection against Omicron breakthrough infections, yet protection against severe COVID‐19 is expected. Neutralizing antibodies against variants of concern were detected up to 2.5 months after the third COVID‐19 mRNA vaccination in adults, whereas some elderly subjects did not have neutralization capacity against Beta and Omicron variants at 1 month after third dose. Single mRNA vaccine after SARS‐CoV‐2 infection induced comparable antibody levels.